Characterization of Escherichia coli strains producing heat-stable enterotoxin b (STb) isolated from humans with diarrhea. - Lortie, L A (1991)
Two of 49 cytolethal distending toxin-producing strains of Escherichia coli isolated from human stools contained the gene coding for heat-stable enterotoxin b (STb), as detected by a colony hybridization assay. The STb gene was found to be on a 70-kb plasmid also coding for heat-labile enterotoxin (pLT-I). Restriction endonuclease analysis showed the STb gene from human isolates to be similar to the STb gene found in porcine strains. Moreover, by enzymatic amplification based on oligonucleotide primers designed from a porcine STb sequence, the expected portion of the STb gene was amplified for the human E. coli strains. The STb enterotoxin from these strains was bioactive in rat jejunal loops and was detected with an enzyme-linked immunosorbent assay by using polyclonal antiserum raised against purified porcine STb toxin.